Beyond perfection - the pianist Arturo Benedetti Michelangeli - Brahms, Johannes 1833-1897 (3B-Produktion, 2019)
Arturo Benedetti Michelangeli - a name that provokes almost a sense of awe and intimidation, even among his piano-playing peers. It is a name that represents the highest degree of perfection, a quest for beauty that surpasses that of any other piano virtuoso. However Michelangeli also had a reputation for cancelling concerts at short notice and was consequently portrayed in the media as a somewhat neurotic artist. "Beyond Perfection - Arturo Benedetti Michelangeli" is the result of a 30-year search that has resulted in unusual interviews with those who knew him, and has also uncovered a wealth of new archive material: We get to experience Arturo Benedetti Michelangeli as he has never been seen before - and more importantly, as he has never been heard before. We also witness the maestro's struggle back to his former perfection after suffering a devastating heart attack. This homage to Michelangeli provides the first comprehensive and in-depth portrait of a brilliant pianist who achieved mythical status
Bildformat: Breitbild (1,78:1)
Filmed in HD, historic material remastered for HD
A production of 3B-Produktion, SWR/arte, Unitel, SRF, MFG Baden-Württemberg, 2019. Artwork & editorial © 2020, C Major Entertainment
Keywords: Benedetti Michelangeli, Arturo -- 1920-1995; Pianist; Italien; Film; Interview; DVD-Video